Analysis of Rain Water and Runoff Water Quality through The Medium of Sand and Zeolite on Green Roof based on Physical and Chemical Parameters - Agustia, Sinta; Wirasembada, Yanuar C.; Saptomo, Satyanto K.; Chadirin, Yudi (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
Reduced urban green space (RTH) can decrease the rainwater catchment area so that groundwater reserves are reduced. Another source of raw water that can be exploited is rainwater. Green roof can be used as a rainwater catchment area in order to increase urban green space and simple rainwater filtration by medium. Therefore, it is necessary to test the quality of rainwater and green roof runoff water. The purpose of this research is to analyze and determine the quality of rainwater and green roof runoff water with sand and zeolite as media. The water quality standard reffered to Government Regulation No. 82/2001 regarding the water quality management and water pollution control. Determination of water quality are using STORET method refferred to Ministry of environment’s Decree No. 115/2003 regarding the guidance of water quality status. Rain water and green roof runoff  water with all various media are classified as lightly polluted and have potensial as a raw water source for daily consumptions.